Fishing down nutrients on coral reefs - Allgeier, Jacob E. (Nat Commun, 2016)
Fishing is widely considered a leading cause of biodiversity loss in marine environments, but the potential effect on ecosystem processes, such as nutrient fluxes, is less explored. Here, we test how fishing on Caribbean coral reefs influences biodiversity and ecosystem functions provided by the fish community, that is, fish-mediated nutrient capacity. Specifically, we modelled five processes of nutrient storage (in biomass) and supply (via excretion) of nutrients, as well as a measure of their multifunctionality, onto 143 species of coral reef fishes across 110 coral reef fish communities. These communities span a gradient from extreme fishing pressure to protected areas with little to no fishing. We find that in fished sites fish-mediated nutrient capacity is reduced almost 50%, despite no substantial changes in the number of species. Instead, changes in community size and trophic structure were the primary cause of shifts in ecosystem function. These findings suggest that a broader perspective that incorporates predictable impacts of fishing pressure on ecosystem function is imperative for effective coral reef conservation and management.